News sources: distinct usage of sources by the Wall Street Journal and the Telegraph in reporting special issues on Islam and Muslims in Malaysia and Indonesia - Hassan, Fauziah; Omar, Siti Zobidah; Hassan, Md. Salleh; Ahmad Ghazali, Akmar Hayati; Othman, Siti Suriani (Medwell Journals, 2016)
News sources are the main important element in news reporting as its function is to ensure that the particular news content is reliable and can be trusted. Thus, this empirical study generally intends to identify the pattern of the news sources used to report on special issues on Islam and Muslims predominantly in Malaysia and Indonesia. This study was conducted by selecting the Wall Street Journal and the Telegraph newspapers as samples for the study. The news samples have been selected from 2012 until 2014. The objectives of this study are to see the pattern of news sources used by these two newspapers and also to compare the sources used within the chosen time frame of the study. The data was collected based on the preliminary study and a total of 445 news paragraphs have been analysed through NVivo 8. However, only 186 of news paragraph mentioned its news sources. The findings presented that 149 of news paragraph used official sources which have been classified into media, institutional, leader and minister. While, only 37 news paragraphs used unofficial sources which consists of civilian, activist, witnesses and victims. From this preliminary data, it can be said that both of the newspapers quoted the news from official sources compared to unofficial sources to report issues relates to Islam and Muslims in Malaysia and Indonesia.